P357 Remote ischemic post-conditioning may prevent cardiac remodeling within two years of STEMI by cardioprotective microRNA upregulation. (17th January 2020) - Ikonomidis, I; Vlastos, D; Katsanos, S; Gazouli, M; Thymis, J; Triantafyllou, C; Varoudi, M; Andreadou, I; Triantafyllidi, H; Makavos, G; Kapelouzou, A; Vrettou, A R; et al.
Abstract: Background: Remote ischemic post-conditioning attenuates ischemia-reperfusion injury in patients with STEMI. However, its biochemical mechanisms, including micro-RNA expression, and effects on cardiac remodeling have not been deﬁned. Methods: We examined 80 patients with STEMI and 20 healthy controls. All patients had been evaluated by cardiac echocardiography. The conditioning protocol utilised a single ischemic stimulus by brachial cuff inﬂation of both arms at 200mmHg for 5 minutes, while 20 patients underwent a sham conditioning procedure by way of cuff inﬂation omission after its placement. Blood samples were taken before and after the conditioning protocol; thus, the expression of microRNA-144, -150, -499 (cardioprotective action), -21, and -208 (remodeling stimuli) was quantiﬁed at baseline and after the ischemic conditioning procedure, by polymerase chain reaction. Additionally, cardiac remodeling was evaluated by repeat echocardiography after a 2-year follow-up period, in 40 patients. Results: Our conditioning protocol resulted in a statistically signiﬁcant increase in miR-144, -150, -499, -21, and -208 expression (55.9 vs 7.4/U6sn, p < 0.001; 3.4 vs 1.8/U6sn, p < 0.05, p = 0.01; 3.5 vs 1.6/U6sn, p < 0.001; 2.1 vs 1.2/U6sn; 2.4 vs 1.9/U6sn) compared to baseline; none of the aforementioned measurements was affected by the sham procedure. Furthermore, both left-ventricular end-diastolic (LVEDV) and end-systolic volume (LVESV) were decreased after the 2-year follow-up period (from 99.3 ± 6.7 to 85.9 ± 5.7, p= 0.004, and from 55.3± 6.1 to 48.6± 5.2, p= 0.04, respectively). In addition, the increase in mir-144 and mir-499 was signiﬁcantly correlated with a decrease in LVESV (r=-0.355, p < 0.05; r=-0.368, p < 0.05, respectively), while the increase in mir-499 was also signiﬁcantly correlated with a decrease in LVEDV (r=-0.374, p < 0.05) at follow-up. Conclusion: Remote ischemic conditioning may prevent adverse myocardial remodelling within 2 years of the index ischemic event, likely by up-regulation of cardio-protective microRNAs expression.